Flow paths and variability of the North Atlantic Current: A comparison of observations and a high-resolution model - Breckenfelder, Tilia; Rhein, Monika; Roessler, Achim; Böning, Claus W.; Biastoch, Arne; Behrens, Erik; Mertens, Christian (Journal of Geophysical Research: Oceans, 2017)
The North Atlantic Current (NAC) is subject to variability on multiannual to decadal time scales, influencing the transport of volume, heat, and freshwater from the subtropical to the eastern subpolar North Atlantic (NA). Current observational time series are either too short or too episodic to study the processes involved. Here we compare the observed continuous NAC transport time series at the western flank of the Mid-Atlantic Ridge (MAR) and repeat hydrographic measurements at the OVIDE line in the eastern Atlantic with the NAC transport and circulation in the high-resolution (1/20°) ocean model configuration VIKING20 (1960–2008). The modeled baroclinic NAC transport relative to 3400 m (24.5 ± 7.1 Sv) at the MAR is only slightly lower than the observed baroclinic mean of 27.4 ± 4.7 Sv from 1993 to 2008, and extends further north by about 0.5°. In the eastern Atlantic, the western NAC (WNAC) carries the bulk of the transport in the model, while transport estimates based on hydrographic measurements from five repeated sections point to a preference for the eastern NAC (ENAC). The model is able to simulate the main features of the subpolar NA, providing confidence to use the model output to analyze the influence of the North Atlantic Oscillation (NAO). Model based velocity composites reveal an enhanced NAC transport across the MAR of up to 6.7 Sv during positive NAO phases. Most of that signal (5.4 Sv) is added to the ENAC transport, while the transport of the WNAC was independent of the NAO.